Relationship between body composition and the level of aerobic and anaerobic capacity in highly trained male rowers - Durkalec-Michalski, K.; Nowaczyk, P. M.; Podgórski, T.; Kusy, K.; Osinski, W.; Jeszka, J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Body composition may affect the potential for success in sports. For this reason, our study aimed to determine the impact of body composition on the level of aerobic and anaerobic capacity in competitive rowers. METHODS: The study involved 48 males aged 20±2 years. Body composition was analysed using electrical bioimpedance. Maximum aerobic capacity (VO2max) and average anaerobic power (AP) were determined using an incremental cycling test until exhaustion and a standard Wingate Anaerobic Test (WAT), respectively. RESULTS: The optimal ranges of body components with respect to the level of anaerobic and aerobic capacity at preparatory period for highly trained rowers aged 17-23 years, with body mass 67.5-104.7 kg, were 86-88% for fat free mass (FFM), 63-65% for total body water (TBW) and 11-13% for fat mass (FM). Regression analyses showed that BM and FFM significantly contributed to the prediction of VO2max and AP. The increase in FFM and BM by 1 kg resulted in the change of VO2max by +0.161 l/min and -0.057 l/min, and AP by +5.51 W and +4.74 W, respectively. CONCLUSIONS: Body composition is closely related to the level of aerobic and anaerobic capacity in rowers, and we suggest that its regulation can serve as an effective tool to improve physical performance. The regression models we developed seem to be promising for estimating the changes in physical capacity based on body composition modifications, however, their accuracy should be verified in an experimental study.